2022
DOI: 10.1055/s-0041-1740583
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Hospital-Acquired Pneumonia/Ventilator-Associated Pneumonia

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a common cause of hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP). MRSA pneumonia is associated with significant morbidity and mortality. Several virulence factors allow S. aureus to become an effective pathogen. The polysaccharide intracellular adhesin allows for the production of biofilms, some strains can produce capsular polysaccharides that protect against phagocytosis, microbial surface components recognizing adhesive matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…All patients (n = 89) infected with MRSA died during the study period. Different studies have reported that respiratory tract infections caused by MRSA strains not only delay the process of treatment and recovery but also increase the mortality rate in the patients admitted to ICUs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…All patients (n = 89) infected with MRSA died during the study period. Different studies have reported that respiratory tract infections caused by MRSA strains not only delay the process of treatment and recovery but also increase the mortality rate in the patients admitted to ICUs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…They also define alpha-toxin as an essential virulence determinant during the interaction of Candida albicans with Staphylococcus aureus in intra-abdominal infection and describe a novel mechanism by which a human pathogenic fungus can increase the virulence of a highly pathogenic bacterium [25] . One of the most important virulence factors secreted by Staphylococcus aureus is α-hemolysin exotoxin, which can result in methicillin-resistant pneumonia that can present as a mild respiratory infection or severe respiratory failure and septic shock [26] . In addition, if this pathogen is persistent, it can cause mastitis, which produces several virulence factors, including enterotoxins [27] .…”
Section: Virulencementioning
confidence: 99%
“…37 It is considered one of the most critical global health threats due to its high pandemic potential. [37][38][39][40][41] Namely, the MRSA strains create an emerging challenge for health systems by increasing the costs associated with the recovery of patients. 42 Epidemiologically, MRSA stands out for efficient dissemination and establishment in environments as diverse as hospitals and communities and is related to different types of productive livestock, whose repercussions range from human health to food production and safety.…”
Section: Introductionmentioning
confidence: 99%